Endothelial function in patients with metabolic syndrome and erectile dysfunction: a question of Angiopoietin imbalance?. (19th June 2013) - Tomada, N.; Tomada, I.; Botelho, F.; Pacheco‐Figueiredo, L.; Lopes, T.; Negrão, R.; Pestana, M.; Cruz, F.
Summary Erectile dysfunction (ED) is a highly prevalent disease whose aetiology is mostly vasculogenic. It is nowadays considered a marker of future cardiovascular events reflecting the underlying endothelial dysfunction, the common link with the metabolic syndrome (MetS). The recent association between MetS, endothelial dysfunction and peripheral artery disease, but not with coronary artery disease (CAD), suggests that the pathophysiologies of CAD and peripheral artery disease may be distinct. Moreover, several recent studies support an emerging role for an imbalance of angiogenic growth factor levels like Angiopoietin 1 and 2 in cardiovascular disease, considering its intimate association with chronic low‐grade inflammation. We aim to find a correlation between Angiopoietins levels and systemic and local endothelial function in MetS and ED patients. Forty‐five MetS patients with ED were enrolled. ED severity was assessed by International Index of Erectile Function questionnaire (IIEF5) and penile duplex Doppler ultrasound (PDDU). Endothelial function was assessed by Peripheral arterial tonometry (PAT), and serum asymmetric dimethylarginine (ADMA), Ang1 and Ang2 levels. Obesity and hypertension were the most frequent MetS parameters (91.1 and 88.9% respectively). Severe ED was present in 35.6% of patients. Penile haemodynamic was impaired in 77.5%. Endothelial dysfunction (PAT criteria) was present in 40.9% of patients. Ang2 levels were significantly higher in men with abdominal obesity. We observed an inverse correlation between Ang1 and peak systolic velocity, and in patients with penile arterial dysfunction, Ang1 levels were significantly higher and Ang2/Ang1 ratio significantly lower, than patients with normal arterial function. Neither ADMA nor PAT parameters were correlated with ED severity evaluated by IIEF5 or PDDU exam. In conclusion, there is an imbalance of angiopoietins in MetS and ED patients. The absence of correlation with PAT or ADMA levels suggests that angiopoietins may be early markers of endothelial dysfunction in this population of higher cardiovascular risk.